Sesquiterpene Lactones from Cotula cinerea with Antibiotic Activity against Clinical Isolates of Enterococcus faecalis - Alessio Cimmino; Emanuela Roscetto; Marco Masi; Angela Tuzi; Imene Radjai; Chakali Gahdab; Rossella Paolillo; Amedeo Guarino; Maria Rosaria Catania; Antonio Evidente (MDPI AG, 2021)
Cotula cinerea, belonging to the tribe Anthemideae, is a plant widespread in the Southern hemisphere. It is frequently used in folk medicine in North African countries for several of its medical properties, shown by its extracts and essential oils. The dichloromethane extract obtained from its aerial parts demonstrated antibiotic activity against Enterococcus faecalis and was fractionated by bioguided purification procedures affording five main sesquiterpene lactones. They were identified by spectroscopic methods (NMR and ESIMS data) as guaiantrienolides, i.e., 6-acetoxy-1β-,6-acetoxy-1α-, and 6-acetoxy-10-β-hydroxyguaiantrienolide (1-3), and germacrenolides, i.e., haagenolide and 1,10-epoxyhaagenolide (4 and 5). The absolute configuration was assigned by applying the advanced Mosher's method to haagenolide and by X-ray diffraction analysis to 1,10-epoxyhaagenolide. The specific antibiotic and antibiofilm activities were tested toward the clinical isolates of Enterococcus faecalis. The results showed that compounds 3-5 have antibacterial activity against all the strains of E. faecalis, while compound 2 exhibited activity only toward some strains. Compound 1 did not show this activity but had only antibiofilm properties. Thus, these metabolites have potential as new antibiotics and antibiofilm against drug resistant opportunistic pathogens.